An ERP investigation of transposed-word effects in same-different matching. (12th March 2021) - Pegado, Felipe; Wen, Yun; Mirault, Jonathan; Dufau, Stéphane; Grainger, Jonathan
Abstract: Can several words be read in parallel, and if so, how is information about word order encoded under such circumstances? Here we focused on the bottom-up mechanisms involved in word-order encoding under the hypothesis of parallel word processing. We recorded EEG while participants performed a visual same-different matching task with sequences of five words (reference sequence followed by a target sequence each presented for 400 ms). The reference sequence could be grammatically correct or an ungrammatical scrambling of the same words (e.g., he wants these green apples/green wants these he apples). Target sequences for 'different' responses were created by either transposing two words in the reference (e.g., he these wants green apples/green these wants he apples), or by changing two words (e.g., he talks their green apples/green talks their he apples). Different responses were harder to make in the transposition condition, and this transposed-word effect started to emerge around 250 ms post-target onset. The transposed-word effect was first seen on an early onsetting N400 component, with reduced amplitudes (i.e., less negative ERPs) in the transposed condition relative to a two-word replacement condition. A later transposed-word effect was seen on a more temporally widespread positive-going component. Converging behavioral and EEG results showed no effects of reference grammaticality on 'different' responses nor an interaction with transposed-word effects. Our results point to the noisy, bottom-up association of word identities to spatiotopic locations as one means of encoding word order information, and one key source of transposed-word effects. Highlights: Transposed-word (TW) effect in same-different task observed at behavior and ERPs. TW effect starting 250 ms, with the bulk of an early N400 between 300 and 400 ms. The TW effect then reversed in a later and sustained positive component. Results suggest a bottom-up noisy spatiotopic location of word identities.